The 'gravity' of quality: research quality and the attractiveness of universities in Italy. Issue 10 (3rd October 2019) - Bratti, Massimiliano; Verzillo, Stefano
ABSTRACT: This paper investigates whether or not research quality is significantly associated with a university's ability to attract students from other provinces in Italy. First-university enrolments of students over the period 2003–11 are regressed on universities' research-quality indicators computed from various bibliometric databases using fixed-effects gravity models. The estimates suggest that research performance is a significant predictor of student enrolment, with estimated elasticities between 0.013 and 0.059, depending on the indicator used.